Numerical investigation of a metal hydride reactor with multi-scale heat transfer Enhancements: Helical coils and porous wall treatments - Alireza Daneh-Dezfuli; Muwafaq Mohammed Jalood; Ebrahim Hajidavalloo (Case Studies in Thermal Engineering)
In this study, a three-dimensional numerical model is developed to investigate the charging performance of a metal hydride-based hydrogen storage tank, with emphasis on the effects of helical coil heat exchanger geometry and operational parameters. Heat transfer and hydrogen absorption in an Mg2Ni tank with helical coil using the finite element method. Results show that increasing the number of coil turns from 6 to 20 reduces the average bed temperature from 574.9 K to 542.8 K and raises the hydrogen concentration from 0.85 to 0.95 at 3000 s. Increasing the coil angle from 1° to 5° decreases the bed temperature from 575.1 K to 538.9 K and increases hydrogen concentration from 0.82 to 0.93. The maximum coil diameter achieves the highest uptake, reducing absorption time by up to 700 s. Enhancing the heat transfer coefficient from 100 to 500 W/m2·K lowers bed temperature from 573.7 K to 538.5 K and raises hydrogen concentration from 0.68 to 0.91. Analysis further reveals that increasing coil pitch number and angle can boost the convective heat transfer coefficient by up to 281 %, but also raises pressure drop by 268 %.